The role of mass media in crisis communication - Reissová, Alice; Žambochová, Marta; Sláma, Vít (Univerzita Pardubice, 2018)
The objective of our work was to identify the role mass media play in crisis communication. We chose the “methanol affair” as an example of a crisis situation which seriously affected the health and lives of people. We wanted to find out whether there are links between the number of published articles and the subsequent volume of spirits sold during the crisis situation in the Czech Republic such as the methanol affair. We used regression analysis and established that the number of articles related to the methanol affair significantly influenced the sales of spirits. The publication of each article was followed by a decrease in sales of spirits and vice versa, i.e., following a decline in the number of articles, sale volumes went up. Negative consequences have also been reported by producers whose annual sales have fallen in a year-to-year comparison. Last but not least, the government also suffered a loss by collecting significantly less money from excise duty as well as other taxes (VAT, income tax). The role of mass media is crucial in crisis communication, businesses should not underestimate the cooperation with mass media and they should be the first to promptly inform the mass media so that they can maintain the confidence of consumers.
Keywords: crisis situation; crisis communication; influence of mass media; decline in sales volumes; excise duty; M37; M19